Reduction of lamin B receptor levels by miR-340-5p disrupts chromatin, promotes cell senescence and enhances senolysis. Issue 13 (28th June 2021) - Herman, Allison B; Anerillas, Carlos; Harris, Sophia C; Munk, Rachel; Martindale, Jennifer L; Yang, Xiaoling; Mazan-Mamczarz, Krystyna; Zhang, Yongqing; Heckenbach, Indra J; Scheibye-Knudsen, Morten; De, Supriyo; Sen, Payel; et al.
Abstract: A major stress response influenced by microRNAs (miRNAs) is senescence, a state of indefinite growth arrest triggered by sublethal cell damage. Here, through bioinformatic analysis and experimental validation, we identified miR-340-5p as a novel miRNA that foments cellular senescence. miR-340-5p was highly abundant in diverse senescence models, and miR-340-5p overexpression in proliferating cells rendered them senescent. Among the target mRNAs, miR-340-5p prominently reduced the levels of LBR mRNA, encoding lamin B receptor (LBR). Loss of LBR by ectopic overexpression of miR-340-5p derepressed heterochromatin in lamina-associated domains, promoting the expression of DNA repetitive elements characteristic of senescence. Importantly, overexpressing miR-340-5p enhanced cellular sensitivity to senolytic compounds, while antagonization of miR-340-5p reduced senescent cell markers and engendered resistance to senolytic-induced cell death. We propose that miR-340-5p can be exploited for removing senescent cells to restore tissue homeostasis and mitigate damage by senescent cells in pathologies of human aging.